A collaborative approach to co-creating contact confident, an evidence-informed tackle safety and technique intervention for coaches and players in Rugby Union - Stodter, A.; McDonald, K.; Salmon, D.; Romanchuk, J.; Evans, N.; Ryan, D.; Taylor, T.; Easton, F.; Peggie, J. (European Journal of Sport Science, 2026)
Training strategies to promote safe and effective tackle technique are an important target for injury prevention and enhancing performance across the rugby codes. However, there is a research-to-implementation gap in `real-world` settings and a need for more studies with women and girls. This article outlines the development of an evidence-informed tackle coaching intervention co-created with content and context experts in women's rugby union. Based on previous work which developed a context-specific injury-prevention programme for women playing Australian Football, a 7-step process was adopted. After gaining organisational support, the process included using research evidence and applied experience and engaging intervention implementers to co-create the content for `Contact Confident`. Iterative integration of feedback from early implementers enhanced practical relevance for coaches. This study underlines the importance of stakeholder collaboration in cocreating and implementing injury prevention interventions, offering a scalable resource for tackle and ball carrier skill development in rugby union for women and girls, with wider relevance for other genders and sports. Future research should look to evaluate the impact of this and similar context-specific interventions on coach behaviour and athlete outcomes across varied global rugby settings.